Community Programs to Control Cancer of The Cervix - Antônio Prudente (Revista Brasileira de Cancerologia, 2023)
Cancer of the Cervix is the site of the disease in which the control measures are more offective. Mass screening is the best way to reach the aims of a public health program. Cervical cancer prevention and detection must be carried out according to the patterns of each community. It is not recommended to limit the examination to pre-symptomatic women, because the general objective of detection is the discovery of cancer cases a good time before it would be done by the initiative of the patients themselves. Mass examination is able to change the general picture of cancer stages at the time of diagnosis. The kind of organization which carries out the detection of cervix cancer does not matter very much. The work can be executed in cancer or general hospitais, in special clinics, in health centers or even in physician’s offices. The simple taking of vaginal smears by unprepared personnel or even by the patient herself cannot be recommended. To co-ordinate the work of the detection units a Central or Basic Unit is necessary. Complete diagnosis and treatment should be only carried out in very well equiped and staffed institutions. These conditions are generally found in cancer hospitais, cancer clinics and in gynecological departments of Universities and high standar general hospitais. A well organized recording system is necessary to an affective follow-up. After-care must be planned, according to the needs and possibilities of each case. Home care is mandatory in advanced cases and is really effective if organized as a Service of the Hospitais. In the special field of cancer of the female genital organs, emphasis must be given to the teaching of physicians in methods of detection and dignosis. To cover the needs of a mass screening program, a great deal of cytologists and pathologists must be provided. The same can be said about cyto-tecnicians. It is not possible to have the examínation performed by gynecologists in every community. General practicioners can be teached and trained in three or for months. Public education must be conducted very carefully, showing the importance of early diagnosis and the advantages of periodical examination. In Brazil, cancer control is carried out through a large net-work of institutions and units under the supervision of the National Service of Cancer of the Ministry of Health. The great majority of these institutions and units are private. 1490 beds in cancer hospital are available. Prevention and detection of cervical cancer are conducted in 43 autonomous Clinics and in the out-patient departments of Cancer University and General Hospitais. Cytology, Schiller’s test and colposcopy are used routinely in most of the Detection Clinics. Biopsy is performed according to the information obtained through the other items. A Mass Screening Program was planned in Brazil. A Pilot Project on Mass examination in the State of Rio de Janeiro is under way. A group of 517.000 women over 30 years of age are assigned for examination. It is expected to cover about 50 per cent of this group, what was already reached in Niteroi, which is the State largest city. 20.000 records were already analyzed. A reduction of the rate of stages III and IV, from 65 to 30 per cent was already obtained. The cancer rate was 2.25 per cent. The experience in a small and undervelloped community, where a wandering medical group performed the examinations is given to show the difficulties and how they can be overcomed.